Lista czystych przeżuwaczy w Pwt 14,5 w przekładzie Septuaginty - Morta, Krzysztof (Verbum Vitae, 2021)
The article discusses the translation of the clean animals list – wild, undomesticated ruminants – found in the Septuagint, Deut 14:5. It is noticeable that the translators who offered equivalents for the Hebrew names of herbivores inhabiting Palestine made use of such exotic fauna specimens like the giraffe. And that poses a question of what motivated the Alexandrian translators to introduce some animals to their rendition that were barely identifiable – or even entirely unidentifiable – in the Egyptian environment. This paper attempts to explain the ensuing confusion. Based on the translated list of clean ruminants, the article also brings up matters related to the ancient tradition of the dating of the Septuagint.